PENINGKATAN PROSES DAN HASIL BELAJAR PKN DENGAN MENGGUNAKAN MODEL PROBING PROMPTING LEARNING DI KELAS VII SMP NEGERI 2 MUARA BUNGO - Asnidar, Asnidar (Jurnal Tunas Pendidikan, 2023)
ABSTRACT The problem in this research is that the learning process and student learning outcomes in Class VII of SMP Negeri 2 Muara Bungo are still low, this is proven by the results of initial observations carried out by researchers of 17 students, only 30% of whom obtained marks in the completion criteria. The cause is that students are less active in the learning process, do not want to ask questions, students' understanding of Civics material is still lacking. The aim of the research is to improve the Civics learning process and outcomes through the application of the probing prompting learning model. This classroom action research consists of two cycles, each cycle consisting of four stages of activities, namely planning, implementation, observation and reflection. The research results show that the use of the probing prompting learning model can improve students' learning processes and outcomes. This can be seen from the increase in the results of the educator process in cycle I with a percentage of 67.7% with fairly good criteria and cycle II with a percentage of 85.3% with good criteria. Meanwhile, student learning outcomes in cycle I were 64.7% and cycle II 82.4. Keywords: Process, learning outcomes, probing prompting